2D hetero-nanostructured reduced-CuNiFe-oxides with self-produced H2O2 Fenton-like photocatalysis for tetracycline degradation. Issue 2 (5th December 2022) - Fu, Lin; Wu, Dandan; Wen, Ming; Zhu, Yuanzheng; Wu, Qingsheng; Zhou, Tao; Fu, Yongqing
Abstract : Heterostructured reduced-CuNiFe-MMOs nanosheets with multiphases have been fabricated and applied as a Fenton-like photocatalyst, exhibiting efficient, environmentally friendly tetracycline degradation without additional oxidants. Abstract : Fenton-like photocatalysis, an advanced oxidation technology, is considered a promising method by which to degrade tetracycline antibiotic (TC) pollutants, but it remains a challenge to achieve a high degradation efficiency in an environmental friendly way. Herein, cluster structures assembled by 2D nanosheets of reduced CuNiFe mixed-metal-oxides (re-CuNiFe-MMOs) have been synthesized through a combined hydrothermal and polyols-solvothermal reduction process. The synergistic effect induced by multiphases of MMOs and the CuNi alloy endows the obtained re-CuNiFe-MMOs with superior Fenton-like photocatalytic activity for the degradation of TCs without the use of any additional oxidants, which is mainly attributed to the reactive oxygen species (of which ˙O2 − is dominant) generated under visible light based on the synergy of the multiphases. The degradation rate of TC reaches 100% in just 4 minutes with a constant reaction rate of 1.65 min −1, and this can be maintained at 95.5% after 12 cycles. This study provides an environmentally friendly approach for the treatment of antibiotic pollutants directly using visible light.